CIRI SEMANTIK PEMBEDA SATUAN LINGUAL YANG MENGANDUNG MAKNA âCOOKINGâ DALAM BAHASA INGGRIS - , Ibnu Eko Setiawan ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research discusses about the distinctive semantic features on linguistic units which mean âcookingâ. In this research, there are three issues of the problems. They are: what are the linguistic units that mean âcookingâ in English, how is the semantic features of those linguistic units, and how the semantic features of the polisemy of each linguistic units formedâis there any semantic features which maintained from the diverse meanings. This research is a descriptive qualitative research, which requires the description of the data based on the fact found so the descriptions related to the actual situation. The data of this research are sentences, paragraphs or oral discourses and writings containing the words/phrases which mean âcookingâ. The objects of this research are linguistic units which are the hyponymy of âcookingâ. The data obtained in this research were from the spoken form (verbal data) and written form. Verbal data were collected from several culinary experts who were native English speakers and Indonesian chefs who were able to speak English. The other forms of data were taken from the English dictionaries, recipe books, and culinary articles on the internet. The data was then analyzed using the techniques of analyzing the components of semantic features of the semantic units. The results of this research shows that there are, at least, 29 linguistic units (included words and phrases) which are included as the hyponyms of âcookingâ. Those linguistic units are next classifed into three categories. They are: cooking activity which used the convective heat transfer through water, cooking activity which used the convective and conductive heat transfer through oil, and cooking activity using the dry-heat. Based on the analysis of polysemy from the data found, it can be concluded that the linguistic units with the phrase form and borrowing words have less polysemy than those which form as a single word.